Analisis Perkembangan Masa Pranatal - Lauren Rahmadona; Jesika Indriani; Nurli Hayati; Linda Yarni (Lembaga Pengembangan Kinerja Dosen, 2024)
The research aims to analyze knowledge about child development in the prenatal or prenatal period starting from understanding prenatal development, characteristics of the prenatal period, and the prenatal development period. The research method used in this research is library research. Data collection techniques use library research in the form of books, journals and other studies. The data analysis technique uses descriptive analysis. The research results show that prenatal or prenatal development begins at fertilization until birth, which occurs around nine months. The characteristics include a mix of characteristics inherited from both parents of the fetus, the influence of conditions in the mother's body, gender certainty, rapid growth, contain many physical and psychological dangers, and the formation of new attitudes. The prenatal development period lasts for 280 days or 40 weeks which is calculated from the first day of the last menstruation which consists of 3 periods starting from the Zygote period, Embryo period and Fetus period..